2012
DOI: 10.1159/000338126
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anti(myco)bacterial Interventions in the Management of IBD: Is There Evidence at All?

Abstract: Background/Aims: The etiology of IBD is unknown but may relate to an unidentified bacterial pathogen or an immunological reaction to gut microbiota. Antibiotics have therefore been proposed as a therapy for Crohn’s disease (CD) and ulcerative colitis (UC). The aim of this review was to compel the evidence for the use of antibiotics in the treatment of IBD. Methods: We performed a systematic review of the literature regarding the use of antibiotics for inducing or maintaining remission in IBD. Results: Current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 178 publications
1
10
0
Order By: Relevance
“…Unexpectedly, fungi-depleted mice exhibited aggravated colitis manifested by increased weight loss, histological score, and proinflammatory cytokine production and decreased colon length. However, intestinal inflammation was alleviated in bacteria-depleted mice, consistent with previous studies 32 . Therefore, we hypothesized that bacteria are the major driving force in acute enteric inflammation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unexpectedly, fungi-depleted mice exhibited aggravated colitis manifested by increased weight loss, histological score, and proinflammatory cytokine production and decreased colon length. However, intestinal inflammation was alleviated in bacteria-depleted mice, consistent with previous studies 32 . Therefore, we hypothesized that bacteria are the major driving force in acute enteric inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…IBD patients and animal models commonly have an abundance of gut bacteria in the inflamed mucosa, and antibiotics effectively attenuate intestinal inflammation 31 32 . We tested whether colitis can be mitigated by eliminating gut fungi, which also gather in the inflamed mucosa, by evaluating the severity of acute DSS-colitis in bacteria-depleted and fungi-depleted mice.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic treatment is considered first-line treatment for pouchitis. However, only small placebo-controlled trials have been conducted to support this practice and none in children (365,366). Ciprofloxacin may be slightly more effective than metronidazole, with fewer adverse Copyright © ESPGHAN and NASPGHAN.…”
mentioning
confidence: 99%
“…This suggests that in IBD, the myco- and microbiome have a mutual influence on each other. Pointing to the role of the bacteria and microbial dysbiosis in IBD, a study that reviewed randomised controlled trials found significant effects of broad-spectrum antibiotics in the treatment of active CD and active UC [51]. Taken together, these studies suggest that bacterial dysbiosis in the gut, and the richness and diversity of the mycobiome, are important in IBD susceptibility.…”
Section: The Gut Mycobiome and Disease Susceptibilitymentioning
confidence: 99%